Export Spillover Effects: Evidence from Vietnam - MINH, Ngo Ngoc (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019DO - 10.14505//jarle.v10.4(42).21, 2019)
The purpose of this paper is to examine export spillover effects from foreign invested enterprises (FIEs) to domestic manufacturing and processing firms in the North of Vietnam. The paper extracted panel data from comprehensive surveys on manufacturing and processing enterprises in the North of Vietnam conducted by the General Statistics Office in 2016-2018 period including 14,664 observations. The two export equations of the Heckman model were estimated simultaneously by the Maximum Likelihood Estimator method (MLE) and used strong standard errors (Robust Standard Errors). The empirical results showed that the presence of FIEs created a spillover effect on Vietnam’s decision to export goods. Moreover, the export spillover effect depends on the characteristics of domestic enterprises. Particularly, private enterprises with old ages or owns a high level of capitalization will benefit from export spillover effects.